Development ICARE based digital module integrated with sets approach to digestive system concept in Senior High School - Djamahar, Refirman; Tristina, Anzelina; Mahrawi, Mahrawi; Rifqiawati, Ika (Jurnal Pijar Mipa, 2023)
The limitations of learning resources can be felt in several aspects of the quality and quantity, form and types of learning resources available. Meanwhile, learning resources must be available quickly to realize effective learning, allowing students to push themselves to meet independent learning needs. Digital modules continue to be developed by researchers to support the independent learning process. This study aimed to establish teaching products in ICARE-based digital modules integrated with the SETS approach to the digestive system concept in senior high schools. The type of research used is research and development with the 4D model design by Thiagarajan, which consists of 4 stages: define, design, development, and disseminate. The result of the expert assessment ICARE-based digital module received the very feasible category, as the user responses test, the module got a very conceivable category. The Teacher response test got the highest score, with the grammar aspect getting the highest among other elements. This is because the language used in the module is an interactive language. Based on the result, ICARE-based digital modules can be used in the biology learning process, especially in the digestive system.